Simian homologues of human herpesviruses and implications for novel viral introduction to free‐living mountain gorillas. Issue 1 (19th October 2022) - Smiley Evans, Tierra; Lowenstine, Linda J.; Ssebide, Benard; Barry, Peter A.; Kinani, Jean Felix; Nizeyimana, Fred; Noheli, Jean Bosco; Okello, Ricky; Mudakikwa, Antoine; Cranfield, Michael R.; Mazet, Jonna A. K.; Johnson, Christine K.; et al.
Abstract: The endangered mountain gorilla ( Gorilla beringei beringei ) in Rwanda, Uganda, and the Democratic Republic of Congo is frequently in contact with humans through tourism, research activities, and illegal entry of people into protected gorilla habitat. Herpesviruses, which are ubiquitous in primates, have the potential to be shared in any setting where humans and gorillas share habitat. Based on serological findings and clinical observations of orofacial ulcerated lesions resembling herpetic lesions, an alpha‐herpesvirus resembling human herpes simplex virus type 1 (HSV‐1) has long been suspected to be present in human‐habituated mountain gorillas in the wild. While the etiology of orofacial lesions in the wild has not been confirmed, HSV‐1 has been suspected in captively‐housed mountain gorillas and confirmed in a co‐housed confiscated Grauer's gorilla ( Gorilla beringei graueri ). To better characterize herpesviruses infecting mountain gorillas and to determine the presence/absence of HSV‐1 in the free‐living population, we conducted a population‐wide survey to test for the presence of orally shed herpesviruses. DNA was extracted from discarded chewed plants collected from 294 individuals from 26 groups, and samples were screened by polymerase chain reaction using pan‐herpesvirus and HSV‐1‐specific assays. We found no evidence that human herpesviruses had infected free‐ranging mountain gorillas. However, we found gorilla‐specific homologs to human herpesviruses, including cytomegaloviruses (GbbCMV‐1 and 2), a lymphocryptovirus (GbbLCV‐1), and a new rhadinovirus (GbbRHV‐1) with similar characteristics (i.e., timing of primary infection, shedding in multiple age groups, and potential modes of transmission) to their human counterparts, human cytomegalovirus, Epstein‐Barr virus and Kaposi's sarcoma‐associated herpesvirus, respectively. Abstract : Suspected viral lesions with potential herpetic etiology prompting investigation of infectious cause in free‐ranging mountain gorilla populations. Research highlights: Discovery of mountain gorilla‐specific homologs to human herpesviruses, including cytomegaloviruses, a lymphocryptovirus, and a rhadinovirus with similar characteristics to their human counterparts. Human herpes simplex virus type 1 (HSV‐1) has not entered the wild mountain gorilla population despite frequent contact with humans. Any potential future consideration of reintroduction of captive mountain gorillas should carefully consider the possibiliy of introducing HSV‐1 and other human pathogens to the wild population.